Family Childcare Types and Conduct Problem Behaviors in Young Children: The Mediation Role of Caregiver-Child Interaction - Liu, Li; Fan, Lijun; Hou, Xiang-Yu; Wu, Chuan-An; Yin, Xiao-Na; Wen, Guo-Min; Sun, Dengli; Xian, Dan-Xia; Jiang, Hui; Jing, Jin; Jin, Yu; Chen, Wei-Qing (Frontiers in Pediatrics, 2018)
Background: Previous studies have demonstrated the impacts of genetic, family, and community factors on child conduct problems (CPs). However, little is understood regarding the association between family childcare types and child conduct problem behaviors, as well as whether and to what extent caregiver-child interaction mediates the above association. Methods: 9,289 children first entering kindergartens in the Longhua New District of Shenzhen, China were enrolled in this cross-sectional study. Primary caregivers were invited to fulfill a self-administered structured questionnaire containing data regarding socio-demographics, family childcare types, caregiver-child interaction, and child conduct problem behaviors (measured by the Conners’ Conduct Problem Subscale). A series of multiple logistic and linear regression models were employed to assess the associations among family childcare, caregiver-child interaction, and child conduct problem behaviors. Results: Family childcare types other than by parents together (i.e., mother alone, mother with others, grandparents, or changing caregivers) were all significantly associated with higher risks of conduct problem behaviors in young children (adjusted ORs ranged from 2.18 to 2.55, and adjusted βs ranged from 0.043 to 0.073; all p<0.05), after adjusting for confounders including child age, gender, parental education level, parental age at pregnancy, marital status and family income. The following family childcare types (mother alone, or grandparents, or changing caregivers) versus the childcare by parents together showed significant relative indirect effects on conduct problem behaviors through caregiver-child interaction, indicating the significant mediation effect of caregiver-child interaction on the above associations. Mediation of caregiver-child interaction on the effect of being cared by mother with others relative to care by parents together on child conduct problem behaviors was yet non-significant. Conclusions：Family childcare types other than by parents together are associated with increased risks for conduct problem behaviors in young children. Caregiver-child interaction may function as a potential mediator for the above association.